Managerial levers in cultivating new mental space for business innovation - M. Leibold; S. C. Voelpel; E. B. Tekie (South African Journal of Business Management, 2004)
Individuals and organizations have mindsets that reflect how they view themselves and the world around them. Some prominent authors have commented on this phenomenon and its relevance to business innovation. In this article, we refer to these mindsets as `mental space' and define the latter as the way individuals and organizations perceive markets, products, industries, boundaries, strategies and capabilities.A common mental space is often shared inside an organization and among its stakeholders, concerning how they compete in their industry, strategic group, value chains and chosen markets. This collective `conventional wisdom' often perpetuates itself and proves to be ineffective when major discontinuous changes take place in the business environment. Incumbent (industry-established) organizations face the challenge of developing or nurturing new mental space that enables faster innovation inside and across traditional boundaries, especially in an era increasingly characterized by the phenomenon of `open' and `networked' innovation.Despite the fact that recent business literature and prominent authors emphasize the importance of creativity and innovation for organizations in a turbulent environment, there seems to be lack of a clear definition and guidelines for cultivating new mental space for such activities and processes. By drawing from the extant strategic management literature and relevant business examples, this article suggests managerial levers for cultivating new mental space to drive organizational innovation to higher and appropriate levels for its proactive sustainability.
Keywords: 650